2005
DOI: 10.1007/s10694-005-4629-3
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Double Glazing in Corner Fires

Abstract: The results of fifteen experiments in which a double glazing assembly was exposed to enclosure fires of increasing severity are presented. The glazing assembly was exposed to the typical two zone or one zone fire enclosure environment with consistency and repeatability within each set of three experiments conducted at each severity level, evident from the enclosure gas temperature profiles. The results presented include; enclosure local gas temperatures, local exposed glass surface temperatures, local shaded g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…4 (c) and (d) demonstrate the HRR of tests with 2 kg and 6 kg fuel mass, and it was found that the cracks were normally initiated in the steady stage. However, in enclosure fires, the incident thermal flux is directly proportional to time for the growing period of the fire [21]. As illustrated in Table 3, the critical heat flux was around 10 kW/m 2 for Pane 1, and its threshold value was 5.72 kW/m 2 .…”
Section: (A) and (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…4 (c) and (d) demonstrate the HRR of tests with 2 kg and 6 kg fuel mass, and it was found that the cracks were normally initiated in the steady stage. However, in enclosure fires, the incident thermal flux is directly proportional to time for the growing period of the fire [21]. As illustrated in Table 3, the critical heat flux was around 10 kW/m 2 for Pane 1, and its threshold value was 5.72 kW/m 2 .…”
Section: (A) and (B)mentioning
confidence: 99%
“…Because the experiments were conducted in an open space, the HRR of the pool fire was stabilized. Assuming constant incident heat flux and neglecting convection, the glazing temperature may increase linearly according to the following equation [21]:…”
Section: Temperature and Heat Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, thermal stresses develop increasingly due to temperature differences, and the glass pane will break and even fall out at a certain level. Experimental tests have been carried out to study glass breakage in fires using room calorimeters and bench-scale test facilities [1][2][3][4][5][6]. Gas and surface temperatures and heat fluxes for breaking glass were studied for numerous types of glass.…”
Section: Introductionmentioning
confidence: 99%
“…e issue of glass thermal cracking and fallout has been rst raised in 1980s by Emmons [51] and other researchers [52,53], while in the last decades, an increasing number of experiments have been carried out on small-scale specimens, single glass panes, or double glass panes variably supported, under the e ect of re or heat radiation (see, e.g., [54][55][56][57][58][59][60] …”
Section: Glass Ermomechanical Properties and Temperature E Ectsmentioning
confidence: 99%